Abstract 181: Technical success of the WEB‐17 system for intracranial aneurysms: Summary of the early experience - Amro Elrefaei; Sherief Ghozy; Ahmed Sallam Motawei; Hassan Kobeissi; Charbel Moussalem; David F. Kallmes; Ramanathan Kadirvel (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Background: The Woven Endo‐Bridge (WEB) device is an intrasaccular device being used to secure intracranial aneurysms through the endovascular approach. The WEB is commonly used for wide‐neck aneurysms. There are no comprehensive studies to assess the low‐profile device WEB 17 so far. Although, some single studies have reported their early experience using the device. We plan to provide a comprehensive assessment of the early center experience using the WEB 17 device to secure intracranial aneurysms. Objective: To provide an overview of the early‐center experience of the 0.017‐inch endovascular Woven EndoBridge device (WEB‐17) device. Methods A systematic review and meta‐analysis were conducted following the PRISMA recommendations. On April 15, 2023, we searched for eligible papers in Pubmed, Web of Science (ISI), Scopus, and Embase databases. The meta‐analysis was done using R software version 4.3.0. and the "meta" package. Pooled prevalence (%) and their corresponding 95% confidence intervals (CI), random‐effects model based and the generalized linear mixed models (GLMMs) method. On the presence of multiple follow‐up points, we included the last available in the analysis. Complete occlusion was defined as Raymond–Roy occlusion classification (RROC) class I, and adequate occlusion was defined as RROC class I or II. Results Seven studies were finally included following the double‐reviewer screening of the retrieved literature. The patients' mean age ranged from 52.5±13.8 to 62.0±9.5 years, and 71.0% were females. The mean follow‐up duration ranged from 6±2.25 months to 11.6±4. Technical success was achieved in 98.34% (95% CI= 96.72‐99.17) of the cases, while adjunctive devices were used in 4.97% (95% CI= 1.60‐14.39) of them (Figure 1). The complete occlusion rate was 72.54% (95% CI= 63.44‐80.08) (Figure 2), while the adequate occlusion rate was 94.41 (95% CI= 88.17‐97.46) (Figure 3). There was no significant heterogeneity in all pooled outcomes. Conclusion The early experience of the device shows an efficacy profile comparable with the currently available devices in treating intracranial aneurysms.